2018
DOI: 10.1002/ddr.21461
|View full text |Cite
|
Sign up to set email alerts
|

Dose translation between laboratory animals and human in preclinical and clinical phases of drug development

Abstract: Preclinical Research & Development Appropriate translation and determination of the maximum recommended starting dose in human is a vital task in new drug development and research. Allometric scaling is the most frequently used approach for dose extrapolation based on normalization of dose‐to‐body surface area. Misinterpretation of allometric dose conversion and safety factor application can lead to major problems in calculating maximum recommended safe starting dose in first‐in‐human clinical trials. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
148
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(151 citation statements)
references
References 25 publications
2
148
1
Order By: Relevance
“…From the expected water consumption of the C57BL/6J strain, the selected dose for animals was comparable to a human equivalent dose (HED) of 25 mg kg −1 . This HED value had a close similarity to a pharmacological niacin dose of 1500 mg per day for an adult human of 60 kg.…”
Section: Methodsmentioning
confidence: 84%
“…From the expected water consumption of the C57BL/6J strain, the selected dose for animals was comparable to a human equivalent dose (HED) of 25 mg kg −1 . This HED value had a close similarity to a pharmacological niacin dose of 1500 mg per day for an adult human of 60 kg.…”
Section: Methodsmentioning
confidence: 84%
“…29 These selected doses for animals were comparable to human equivalent doses (HED) of 40 and 80 µg kg −1 . 30 RNA isolation and real-time quantitative PCR analysis RNA from hepatic tissues was isolated to quantify gene expression by RT-qPCR. Total RNA was extracted by using TRIsure Reagent (Bioline).…”
Section: Dosage Informationmentioning
confidence: 99%
“…Estimation of a first-in-human dose is an essential element in the clinical development of a drug for approval by the FDA [22]. Research and development of a drug must be demonstrated in more than one animal species in order to predict human pharmacokinetics [23,24]. The objective of this study was to investigate the pharmacokinetics and bioavailability of mitragynine in healthy female beagle dogs after single oral and intravenous administration.…”
Section: Introductionmentioning
confidence: 99%